23‐3: Distinguished Paper: The New Route for Realization of 1µm‐pixel‐pitch High Resolution Displays. Issue 1 (29th May 2019) - Choi, Ji Hun; Yang, Jong-Heon; Pi, Jae-Eun; Hwang, Chi-Young; Kim, Yong-Hae; Kim, Gi Heon; Kim, Hee-Ok; Hwang, Chi-Sun
Abstract : We present a new pixel structure to realize the 1μm‐pixel‐pitch display. This structure is based on the conventional back‐channel etched thin‐film transistor (TFT), but all layers except the horizontal gate line are vertically stacked on the embedded data line, enabling the implementation of high resolution display panels. The vertically‐stacked TFT with 1μm‐channel length shows a high field effect mobility over 50 cm 2 /Vs, low subthreshold slope of 78 mV/decade. It also shows a high uniform electrical characteristic over the entire 6‐inch wafer. The development of new architecture enables the implementation of a 1μm‐pixel‐pitch high resolution displays such as digital hologram.